ANALISA SISTEM AKUNTANSI PEMBELIAN EKSPOR PADA CV. LINTAS TUJUH BENUA - Farikhah Rohmatul H. (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
Today's export business promises great profit opportunities, such as those run by CV. Lintas Tujuh Benua which specializes in the distribution of food and soft drinks in the international market. This study aims to evaluate whether the company's purchasing process accounting system is able to provide the necessary information and comply with applicable policies. Through the qualitative analysis method, this study describes the purchasing process used by the company and identifies problems in the purchasing accounting system. The application of accounting theory is key in preparing the company's statutory financial statements, explaining how transactions are processed and recording daily financial activities. In the context of purchasing, which involves paying fees to sellers, accounting principles play a crucial role, prompting many companies to switch to web-based accounting systems to improve their operational efficiency